The influence of lifestyle on female fertility. Review of the literature - Śmigielska-Mikołajczyk, Maria Janina; Szostak, Agata; Szeliga, Anna; Szopińska, Kinga; Graca, Magdalena; Korta, Karolina; Oluszczak, Karolina; Dyląg, Liliana; Wawszkowicz, Konrad; Łowicka, Weronika (Quality in Sport, 2024)
Introduction Women who want to get pregnant soon often ask their doctors how to prepare best. During such a visit, doctors usually mention folic acid supplementation, a check-up with the dentist and gynaecologist or vaccinations. However, it is also worth pointing out the importance of lifestyle factors that affect fertility and fetal development. Modifying daily habits can improve fertility naturally and make getting pregnant faster. An increasing number of studies are being published on the importance of nutrition, physical activity, sleep, stress, stimulants and other factors on women's reproductive health. This article is a summary of the current state of knowledge in this area. Aim of the study The aim of this study is to review the literature and summarize current state of knowledge on the association between lifestyle factors and female reproductive function. Material and methods of research This literature review based on researches from PubMed platform. We searched articles describing connection between potentially modifiable lifestyle factors and women’s fertility. Search terms included keywords: „lifestyle”, „female fertility”, „obesity”, „sleep”, „nutrition”, „diet”, „stress”, „physical activity”, „smoking”, „alcohol”, „weight loss”, „reproductive health”.